SERBIAN VOLUNTEERS AND RUSSIAN REVOLUTION OF 1917 - Ia. V. Vishniakov (Vestnik MGIMO-Universiteta, 2017)
Using original documents from the Russian State Military Historical Archive, many of which are introduced for the first time, the author reveals details of creation and activities of the Serbian Volunteer Corps formed from captured soldiers and officers of the Austro-Hungarian army inOdessain the Summer 1916. The same autumn it received a baptism of fire in Dobruja fighting in the separate corps of the Russian army under the command of General Zayonchkovsky. The research interest in studying the activities of “national” and "international" military units within the Russian army is connected with the question of expediency and effectiveness of using such forces against those for whom they have not so long ago shed blood. The author, contrary to the popular opinion of Serbian historians, shows that the call to join the First Serbian division did not arouse mass enthusiasm among the prisoners of war both Serbs and representatives of other Yugoslav nations because of well-founded fears for their close relatives living in the Dual Monarchy and a fairly comfortable stay in the Russian captivity. At the same time, the author emphasizes that this military unit, commanded by officers of the Serbian regular army, was considered by the political leadership ofSerbiaas the basis of the future armed forces of the new state ofYugoslavia. The article shows that the events of the Russian Revolution of 1917 influenced the future fate of this military formation. Many of its soldiers later found themselves on different sides of the front in the Russian civil war. A special attention is payed to the interethnic conflict erupted in the corps between the Serbs on the one side and the Croats and Slovenes on the other. The author introduces a significant body of primary documents showing the nuances of relations in the corps between representatives of various Yugoslav nations. The article emphasizes that the relationship of the Serbs, Croats and Slovenes within the corps became the prologue to the future tragic fate of the Yugoslav state and its army, which were doomed to eventually collapse.